Influence of hydro-pneumatic accumulator on the hydraulic drive of the brush work body of light type track machines - Grinchar N.G.; Bykov A.Yu. (Научно-технический вестник Брянского государственного университета)
The main direction of improving the repair processes of all types and the current maintenance of the track is to reduce the time and labor costs with the highest possible level of mechanization and automation of all types of track work. At the same time, a significant place is occupied by cleaning the tracks from weeds and excess ballast. The working body of the machines for performing these works is a brush picker with flexible blades, which provides cleaning of weeds and ballast below the level of the rail head. As a rule, on domestic machines, flexible blades are segments of a steel cable with a diameter of 16…21 mm. One of the main disadvantages of brush pickers with cable blades is the relatively low efficiency due to fatigue breaking of the flexible blades at the point of exit from the seal. There are also known design solutions with the use of blades made of rubber tape. The most successful is the combination of cable and belt blades on one picker. The main type of drive for such a working body should be considered a volumetric hydraulic drive, which allows you to solve the problem structurally in the simplest and most effective way. Since the picker blades interact with the object (ballast rubble) alternately ( usually there are 8-12 blades) the load on the drive is non-stationary, the pressure in the pressure line of the drive hydraulic motor changes sinusoidally, which negatively affects the reliability and durability of the drive. To smooth out pressure fluctuations, it is recommended to use a hydropneumulator.